Campus landscape environment for student with disabilities: a case of International Islamic University Malaysia (IIUM), Gombak Campus - Mohd Hussain, Mohd Ramzi; Tukiman, Izawati; Zaidin, Nurbazliah; Mohd Shahli, FitryNadia (UPM Malaysia, 2015)
The awareness regarding students with disabilities (SwDs) in campus of higher educational institutions has been increasing. This study investigates the access audit on the proper planning and designing of campus landscape environment which is not only useful for able-bodied people/students but also for the disabled people/students. Preliminary studies have identified challenges in providing accessible built environment in higher educational institutions. The analyzed reviews comprising of design guidelines and suitable landscape designs have been applied to suit the needs of SwDs in the campus landscape environment. This study provides a platform to discover the needs of SwDs, especially in campus environment, based on the type of disabilities and it is important to understand the needs of SwDs before making any decisions. The method of data collection used in this study is the qualitative approach based on case studies, semi-structured interviews, focus group discussions and access audit simulations. The expected outcomes of this study will contribute to design guidelines for outdoor campus landscape, thus allowing the management of universities in Malaysia to upgrade outdoor campus facilities as a whole. The findings will also provide a platform for related organizations to identify the needs of SwDs in higher educational institutions for their support facilities and services in order to help them survive whilst there.